2000
DOI: 10.1073/pnas.070025097
|View full text |Cite
|
Sign up to set email alerts
|

The integral membrane S-locus receptor kinase of Brassica has serine/threonine kinase activity in a membranous environment and spontaneously forms oligomers in planta

Abstract: To gain further insight into the mode of action of S-locus receptor kinase (SRK), a receptor-like kinase involved in the self-incompatibility response in Brassica, different recombinant SRK proteins have been expressed in a membranous environment using the insect cell͞baculovirus system. Recombinant SRK proteins exhibited properties close to those of the endogenous stigmatic SRK protein and were found to autophosphorylate on serine and threonine residues in insect cell microsomes. Autophosphorylation was const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 40 publications
3
36
1
1
Order By: Relevance
“…SRK has been found to be membrane associated, as predicted for a receptor kinase, and has a functional serine/threonine kinase domain [112, 116 -119]. Giranton et al [119] conducted further biochemical studies on SRK using an insect/baculovirus system, and found that the phosphorylation of the recombinant SRK integral membrane protein was constitutive in the absence of pollen or stigma extracts. SRK phosphorylation was shown to occur in trans, whereby a kinaseinactive SRK became phosphorylated when co-expressed with a functional SRK construct likely as a result of SRK dimerization [119].…”
Section: Slg and Srk: Pistil S Proteins And Their Involvement In Selfmentioning
confidence: 99%
See 4 more Smart Citations
“…SRK has been found to be membrane associated, as predicted for a receptor kinase, and has a functional serine/threonine kinase domain [112, 116 -119]. Giranton et al [119] conducted further biochemical studies on SRK using an insect/baculovirus system, and found that the phosphorylation of the recombinant SRK integral membrane protein was constitutive in the absence of pollen or stigma extracts. SRK phosphorylation was shown to occur in trans, whereby a kinaseinactive SRK became phosphorylated when co-expressed with a functional SRK construct likely as a result of SRK dimerization [119].…”
Section: Slg and Srk: Pistil S Proteins And Their Involvement In Selfmentioning
confidence: 99%
“…Giranton et al [119] conducted further biochemical studies on SRK using an insect/baculovirus system, and found that the phosphorylation of the recombinant SRK integral membrane protein was constitutive in the absence of pollen or stigma extracts. SRK phosphorylation was shown to occur in trans, whereby a kinaseinactive SRK became phosphorylated when co-expressed with a functional SRK construct likely as a result of SRK dimerization [119]. Experiments performed to address the physiological relevance of these results examined the oligomeric status of SRK in planta and showed that SRK forms complexes with either other SRK/SLGs or other stigmatic proteins in unpollinated flowers [119].…”
Section: Slg and Srk: Pistil S Proteins And Their Involvement In Selfmentioning
confidence: 99%
See 3 more Smart Citations